2014
DOI: 10.1002/anie.201309260
|View full text |Cite
|
Sign up to set email alerts
|

Trifluoromethylation of Alkenes with Concomitant Introduction of Additional Functional Groups

Abstract: The trifluoromethyl group is found in many synthetic bioactive compounds, and the difunctionalization of a C=C bond, as a powerful strategy for the construction of compounds with various functional groups, has been intensively investigated. Therefore, the difunctionalizing trifluoromethylation of alkenes has attracted growing interest because of the potential of the products as building blocks for bioactive molecules. In this review, we focus on recent advances in the trifluoromethylation of alkenes with conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
146
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 658 publications
(146 citation statements)
references
References 192 publications
0
146
0
Order By: Relevance
“…In contrast to the great success in developing nucleophilic and electrophilic fluoroalkylation reactions, the corresponding asymmetric radical fluoroalkylation versions remain scarce171819, largely because of the intrinsic reactivity of the involved odd-electron species20. On the other hand, intermolecular addition of fluoroalkyl radicals to unactivated alkenes has emerged as one of the most attractive strategies for the direct 1,2-difunctionalization of alkenes to simultaneously construct two vicinal chemical bonds by using a variety of radical fluoroalkyl precursors in racemic form21222324252627. The development of asymmetric catalytic versions of such transformations, however, still remains a formidable challenge with few successful examples.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the great success in developing nucleophilic and electrophilic fluoroalkylation reactions, the corresponding asymmetric radical fluoroalkylation versions remain scarce171819, largely because of the intrinsic reactivity of the involved odd-electron species20. On the other hand, intermolecular addition of fluoroalkyl radicals to unactivated alkenes has emerged as one of the most attractive strategies for the direct 1,2-difunctionalization of alkenes to simultaneously construct two vicinal chemical bonds by using a variety of radical fluoroalkyl precursors in racemic form21222324252627. The development of asymmetric catalytic versions of such transformations, however, still remains a formidable challenge with few successful examples.…”
mentioning
confidence: 99%
“…Within the burgeoning field of radical fluoroalkyl reagents21222324252627, great progress has been made in the direct 1,2-difunctionalization-type fluoroalkylation of alkenes by employing stable fluoroalkylsulfonyl chlorides as the radical sources to in situ generate the desired fluoroalkyl radicals3536373839. For the efficient collection of fundamental yet synthetically formidable chiral β-fluoroalkyl amine-building blocks directly from readily available materials and particularly intrigued by our recent success in asymmetric radical aminotrifluoromethylation of alkenes using a dual-catalytic system of Cu(I) and CPA34, we envisaged the possibility of realizing an unprecedented asymmetric radical aminoperfluoroalkylation and aminodifluoromethylation of alkenes with various fluoroalkylsulfonyl chlorides through such a dual-catalytic system (Fig.…”
mentioning
confidence: 99%
“…Furthermore, in all these Cu-promoted trifluoromethylthiolation reactions, no trifluoromethylated product was observed. Since the substrates have proved to be able to undergo Cu-promoted trifluoromethylation with trifluoromethyl anion, [9, 17] these results (no trifluoromethane and no trifluoromethylation product) further confirmed that trifluoromethyl anion was not the intermediate for the generation of trifluoromethylthio anion.…”
mentioning
confidence: 90%
“…A quick survey of reaction parameters finally revealed that an efficient transformation of our testing substrate, 2-bromoacetophenone with PDFA/S 8 /CsF system was achieved in 74% yield by the addition of CuBr 2 . We proposed that Cu-promoted trifluoromethylthiolation reactions occurred via ligand exchange of SCF 3 − with copper source to generate [CuSCF 3 ] complex, [17,18] followed by addition-reductive elimination to furnish final SCF 3 products. Indeed, we have observed [CuSCF 3 ] complex by 19 F NMR spectrometry in the trifluoromethylthiolation reaction systems (SI, section 5), further supporting this proposed reaction pathway.…”
mentioning
confidence: 99%
“…4 As a consequence, versatile methodologies are being established for the introduction of CF 3 moiety into heterocycles and related organic molecules. [5][6][7][8][9][10][11][12] Copper-catalyzed trifluoromethylation of terminal alkenes through allylic C-H bond activation has been accomplished by Fu and Liu et al exploiting copper catalyst, Umemoto's reagent, and 2,4,6-trimethyl pyridine reaction system (scheme 1, eq 1). 10a In view of recent advances in Cu-catalyzed functionalization of alkenes, 16,17 we envisioned, trifluoromethylation of terminal alkene followed by intramolecular addition of oxygen for the synthesis of trifluoromethylated benzoxazines keeping allylic C-H bond intact (eq 2).…”
mentioning
confidence: 99%